General Education and Special Education Teachers’ Attitudes Towards Inclusion - Hernandez, David A.; Hueck, Susan; Charley, Carmen (Journal of the American Academy of Special Education Professionals, 2016)
The purpose of this study was to examine the difference in general education and special education teachers’ attitudes towards inclusion of students with disabilities and to ascertain if levels of self-efficacy, teacher type, and education level were predictors of teachers’ attitudes towards inclusion. Data were collected from 118 elementary and middle school teachers using an online survey, and a 2-way ANOVA and multiple regression were conducted to answer the research questions. Results indicated that special education teachers’ attitudes towards inclusion were significantly more positive than those of general education teachers and that teacher type and self-efficacy were predictors of teachers’ attitudes towards inclusion. Higher levels of self-efficacy were associated with more positive attitudes towards inclusion. Change in practice may be achieved if school district administrators implement teacher training to improve teacher self-efficacy regarding inclusive practices, which could ultimately improve student outcomes and narrow the achievement gap.